A critical review of lean construction for cost reduction in complex projects - Wong L.S.; Ahmed M.E.A.M. (Jordan University of Science and Technology, 2023)
Construction industry; Lean production; Cost saving; Lean construction; Project cost; Team work; Traditional planning; Cost reduction